2018
DOI: 10.1111/cge.13363
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant spectrum in 265 Chinese patients with hemophagocytic lymphohistiocytosis: Molecular analyses of PRF1, UNC13D, STX11, STXBP2, SH2D1A, and XIAP

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare life-threatening hyperinflammatory disease. This study aimed to investigate the frequencies and distributions of inherited variants in PRF1, UNC13D, STX11, STXBP2, SH2D1A, and XIAP genes in Chinese patients with HLH. A total of 265 patients diagnosed with HLH from January, 2010 to December, 2016 were recruited and analyzed for the 6 genes. Genetic variants were observed in 87 (32.83%) patients. 36 (13.58%) exhibited variants in UNC13D, 18 (6.79%) exhibited PRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to an international survey, approximately 55% of patients with XLP-2 developed HLH and 26% presented with IBD, which was lower that the HLH frequency in Japan (79%), France (71%) and the USA (82%) [ 7 , 10 ]. In a genetic study of 265 Chinese patients with HLH, genetic variants were observed in 87 (32.83%) patients, of which 10 (11.49%) had variants in XLAP and six (6.90%) carried variants in SH2D1A [ 11 ]. EBV infection has been reported to be a trigger of the first HLH episode in patients with XIAP deficiency (30–70% of cases) [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to an international survey, approximately 55% of patients with XLP-2 developed HLH and 26% presented with IBD, which was lower that the HLH frequency in Japan (79%), France (71%) and the USA (82%) [ 7 , 10 ]. In a genetic study of 265 Chinese patients with HLH, genetic variants were observed in 87 (32.83%) patients, of which 10 (11.49%) had variants in XLAP and six (6.90%) carried variants in SH2D1A [ 11 ]. EBV infection has been reported to be a trigger of the first HLH episode in patients with XIAP deficiency (30–70% of cases) [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this extraordinary disease course, the physician performed a genetic test and he was eventually diagnosed with adult FHL. Although primary HLH is commonly diagnosed in children, several examples of genetically confirmed HLH in adults have recently been reported [21][22][23]. Allogenic stem cell transplantation is a recommended therapy for adult primary HLH [23].…”
Section: Discussionmentioning
confidence: 99%
“…No HLH developed in the three reported Japanese XLP2 patients with Glu349del (20). On the other hand, a 1-year-old Chinese male with XIAP Glu349del has been recently reported to present with HLH (21). Patient 3 suffered from severe CD8 + EBV-HLH requiring chemotherapy, which did not recur after the first resolution.…”
Section: Discussionmentioning
confidence: 99%